2011
DOI: 10.1186/1476-511x-10-213
|View full text |Cite
|
Sign up to set email alerts
|

Fish polar lipids retard atherosclerosis in rabbits by down-regulating PAF biosynthesis and up-regulating PAF catabolism

Abstract: BackgroundPlatelet activating factor (PAF) has been proposed as a key factor and initial trigger in atherosclerosis. Recently, a modulation of PAF metabolism by bioactive food constituents has been suggested. In this study we investigated the effect of fish polar lipid consumption on PAF metabolism.ResultsThe specific activities of four PAF metabolic enzymes; in leukocytes, platelets and plasma, and PAF concentration; either in blood cells or plasma were determined. Samples were acquired at the beginning and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 31 publications
3
67
0
1
Order By: Relevance
“…These properties help in reducing atherosclerosis by inhibition of Platelet Activating Factor (PAF, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) responsible for sedimentation, clotting and blocking of coronary channels (Nasopoulou et al, 2011). This action is controlled by down-regulating PAF biosynthesis and upregulating PAF catabolism.…”
Section: Polar Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…These properties help in reducing atherosclerosis by inhibition of Platelet Activating Factor (PAF, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) responsible for sedimentation, clotting and blocking of coronary channels (Nasopoulou et al, 2011). This action is controlled by down-regulating PAF biosynthesis and upregulating PAF catabolism.…”
Section: Polar Fatty Acidsmentioning
confidence: 99%
“…Fatty acids are classified as saturated (no double bond), monounsaturated; MUFA (one double bond) and poly-unsaturated; PUFA (more than one double bond) depending on the presence and number of double between carbon atoms. Other classes of fatty acids include trans-fatty acids and free fatty acids (Williams, 2000) and polar lipids, micro-and macro-constituents of the Mediterranean diet (Nasopoulou et al, 2011). Saturated fatty acid are either short-chain containing 4-12 carbon chains, mid-chain containing 13-16 carbon long chains and long-chain fatty acids of 17-26 carbon chains.…”
Section: Health-related Fatty Acids Common In Human Diet and Their Immentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, PAF can be synthesized by being stimulated with Stap hylococcus aureus toxins or it can be released by Escherichia coli [10]. Given that PAF is an initial trigger in atherosclerosis [11], foodstuffs, which exert antibacterial activities, suppress the production of PAF, and therefore play a positive role in preventing atherosclerosis. Previous studies have demonstrated the lipids extracted from red shrimp brain, marine sponge, sea bass and gilthead sea bream exerted antibacterial activities [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PAF is known to act as an initial trigger in atherosclerosis, and to play a critical role during disease progression (2, 3). The biological actions of PAF are regulated by a specific surface 7-transmembrane-domain receptor (7TMR), which couples to G proteins (4).…”
mentioning
confidence: 99%